Spiritual Leadership of School Administrators with the Development of Professional Ethics - Hongsaipin, Nattapat; Visitthapanyo, PhramahaPisit (Journal of Graduate MCU KhonKaen Campus, 2025)
Spiritual leadership of school administrators and the development of professional ethics are important in bringing colleagues and subordinates to confidence, faith, and trust in school administrators. Adhere to educational institution administrators as role models in conducting oneself in accordance with the educational professional, which leads to the development of professional ethics Spiritual leadership is actually a trait of a person who lives based on faith. true and firm faith in one thing Interaction with what he holds faith until he can feel the spirit that stimulates within the mind a pure mind to behave with a profound understanding of the truth of life. Leaders must be motivated for the common good, indomitable in the face of obstacles, see real value in work and respect for others This life example will affect the faith, faith, determination of the work team or subordinates in devotion to the work without giving any order that being said, if leaders pledge spiritual leadership to the educational administration and development of professional ethics. School administrators must have leadership and insight into the elements of spiritual leadership. In order to be something that will lead to the management of educational institutions and the development of professional ethics. Therefore, if the executives who behave according to the pattern professional standards and strictly defined professional ethics would make them prestige make colleagues and subordinates trust, faith and hope that will lead the organization to success with pride and professional dignity.